Characterisation of spray dried microencapsules with amorphous lutein nanoparticles: Enhancement of processability, dissolution rate, and storage stability. (30th July 2022) - Ding, Zhuang; Wang, Xiao; Wang, Lili; Zhao, Yanna; Liu, Min; Liu, Wenlai; Han, Jun; Prakash, Sangeeta; Wang, Zhengping
Graphic abstract: Highlights: Synthesis of amorphous and crystalline lutein-loaded microencapsulated powders. Amorphous lutein nanoparticles had better breakability than crystalline types. Amorphous lutein formulation showed faster dissolution rate. Amorphous formulation exhibited slower degradation rate. Amorphous lutein forms provide better oral bioavailability for future applications. Abstract: Lutein has limited applicability in the food industry because of its poor water solubility and chemical instability. In this study, amorphous and crystalline lutein-loaded microencapsulated powders were prepared via wet media milling and spray drying techniques. The breakage kinetics, surface morphology, physicochemical characteristics, encapsulation efficiency, dissolution behaviour, and storage stability of the two types of microencapsules were determined. Compared with the crystalline formulation, amorphous lutein nanoparticles displayed better breakability (∼478.8 nm within 20 min) in the milling process and faster dissolution rates under both sink and supersaturation conditions (88.0 ± 1.7% and 47.0 ± 3.8%, respectively, within 2 min). Stability testing revealed that the amorphous formulation exhibited slower degradation rates, with decay constants k of 0.03 and 0.07 at 25 and 40 °C, respectively. Our study results suggest that microencapsules with amorphous lutein nanoparticles represent a commercially viable formulation for maintaining chemical stability and improving oral bioavailability.